Specific Central Nervous System Medications Are Associated with Temporomandibular Joint Symptoms - John K. Drisdale III; Monica G. Thornhill; Alexandre R. Vieira (International Journal of Dentistry)
Aims. There is evidence of association between bruxism and the increasingly common central nervous system stimulants prescribed for attention deficit hyperactivity disorder (ADHD), as well as the selective serotonin reuptake inhibitors (SSRIs) often prescribed for depression or anxiety. However, the evidence is not clear on whether these medications inducing bruxism are directly associated with temporomandibular joint disorder (TMD). The aim of this work is to evaluate whether these medications are associated with TMD symptoms. Methods. Medical history and participant data were obtained for 469 patients from the University of Pittsburgh School of Dental Medicine, Dental Registry and DNA Repository, dating back to 2006. The chi-square test was used to determine any statistically significant associations. Results. There were no statistically significant associations between ADHD stimulant medications or SSRIs and reported TMD symptoms. However, there were significant differences seen between specific brands of medications and reported TMD symptoms. Individuals prescribed methylphenidate (Concerta) were less likely to report temporomandibular joint discomfort (p=0.01). Conversely, individuals prescribed citalopram (Celexa) were more likely to report temporomandibular joint discomfort (p=0.04). Conclusion. Signs and symptoms of temporomandibular joint dysfunction may be influenced by the use of certain medications prescribed for depression or attention deficit hyperactive disorder.